Fisheries and the National Food Security: the Malaysian perspective - Ambak, Mohd Azmi (2000)
Fisheries constitute one of nature’s renewable, highly diverse and dynamic agricultural resources. These resources exist in an aquatic environment that are subjected to an ever increasing degradation, notably pollution. They represent an extremely valuable commodity,much sought after for food, ornaments and recreational purpose. Food is a very important and sensitive topic, especially when a substantial amount of our requirement is produced by others (imported). Shortage of food is detrimental and can create unrest in the country. One of the greatest challenges in the new millenium is to meet the demand for safe and nutritious food for our growing population.